2006
DOI: 10.1897/04-493r.1
|View full text |Cite
|
Sign up to set email alerts
|

Tree swallow (Tachycineta bicolor) exposure to polychlorinated biphenyls at the Kalamazoo River superfund site, Michigan, USA

Abstract: In 1990, a portion of the Kalamazoo River in Michigan, USA, was designated a Superfund site because of the presence of polychlorinated biphenyls (PCBs) in the sediment and floodplain soils. During a four-year period from 2000 to 2003, several avian species were monitored for reproductive effects and concentrations of PCBs in tissues attributed to food chain transfer from contaminated sediments. The tree swallow (Tachycineta bicolor) was chosen as a model receptor for contamination of passerine species. A top-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 34 publications
4
37
1
Order By: Relevance
“…Stomach contents were removed from nestlings and pooled based on proximity to insect sampling grids. Detailed descriptions of sampling methods are described elsewhere (Neigh et al 2006a).…”
Section: Bolus and Tissue Collectionmentioning
confidence: 99%
“…Stomach contents were removed from nestlings and pooled based on proximity to insect sampling grids. Detailed descriptions of sampling methods are described elsewhere (Neigh et al 2006a).…”
Section: Bolus and Tissue Collectionmentioning
confidence: 99%
“…Concentrations of PCBs were significantly greater in tree swallow eggs and nestlings within the Kalamazoo River Superfund site compared to concentrations in birds from an upstream reference location (Neigh et al, 2006a). The risk of PCB-induced effects was determined by comparing site-specific concentrations of PCBs in bird tissues to toxicity reference values (TRVs) determined in controlled laboratory studies with surrogate species (Neigh et al, 2006a).…”
Section: A 123-km Stretch Of the Kalamazoo River In Michigan Was Desmentioning
confidence: 99%
“…The risk of PCB-induced effects was determined by comparing site-specific concentrations of PCBs in bird tissues to toxicity reference values (TRVs) determined in controlled laboratory studies with surrogate species (Neigh et al, 2006a). However, extrapolating from laboratory experiments to tissue concentrations observed in the field has inherent uncertainties (U.S. EPA, 1998).…”
Section: A 123-km Stretch Of the Kalamazoo River In Michigan Was Desmentioning
confidence: 99%
“…Profiles of the relative concentrations of individual PCDD/DF congeners in samples of invertebrates and bolus at SAs on the Tittabawassee River downstream of the source of contamination were dominated by 1,2,3,4,6,7,8,9Introduction Site-specific dietary exposure to polychlorinated dibenzofurans (PCDFs) and polychlorinated dibenzo-p-dioxins (PCDDs) was determined for three cavity-nesting, insectivorous passerine species downstream of Midland, Michigan (USA). Tree swallows (Tachycineta bicolor), which eat primarily emergent aquatic invertebrates (McCarty 1997;McCarty and Winkler 1999;Mengelkoch et al 2004), have been shown to have exposure links to contaminated sediments (Custer et al 1998;Echols et al 2004;Maul et al 2006;Neigh et al 2006c;Papp et al 2007;Smits et al 2005). House wrens (Troglodytes aedon) and eastern bluebirds (Sialia sialis) have been used to assess the contaminant exposure of terrestrial insectivores at locations with contaminated soils (Neigh et al 2006a).…”
mentioning
confidence: 99%